2021
DOI: 10.3390/app11062600
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria Analysis of Alternative Marine Fuels in Sustainable Coastal Marine Traffic

Abstract: Marine transportation is considered to be one of the most important aspects of global transportation services. Due to the increase in marine transportation, there are significant impacts on the marine environment. One of the possible measures for mitigation of the environmental impact could be switching to environmentally friendly fuel. However, the alternative fuel selection process is considered to be a problem due to various criteria to be considered and stakeholders that should be involved in the selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Bilgili provided one comprehensive study of the environmental impact of four fossil marine fuels, concluding that heavy fuel oil (HFO) is a preferable alternative [21], and compared eight alternative marine fuels with LCA, concluding that biogas has the lowest total environmental impact [22]. In addition to these comprehensive studies, a large number of other good studies also exist, e.g., describing individual fuels (LNG [23][24][25][26][27][28][29], methane [30] methanol [31][32][33][34][35], HVO [36,37], hydrogen [38], ammonia [38,39] and electricity [40]), comparing different fuels [9,14,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], or assessing other ways of improving the sustainability of the maritime industry [1,[60][61][6...…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Bilgili provided one comprehensive study of the environmental impact of four fossil marine fuels, concluding that heavy fuel oil (HFO) is a preferable alternative [21], and compared eight alternative marine fuels with LCA, concluding that biogas has the lowest total environmental impact [22]. In addition to these comprehensive studies, a large number of other good studies also exist, e.g., describing individual fuels (LNG [23][24][25][26][27][28][29], methane [30] methanol [31][32][33][34][35], HVO [36,37], hydrogen [38], ammonia [38,39] and electricity [40]), comparing different fuels [9,14,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], or assessing other ways of improving the sustainability of the maritime industry [1,[60][61][6...…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The AHP is a widely used, mature method of determining weights, but it has the disadvantage of poor objectivity. This study used the AHP to first compare the 14 lowest-level indicators; determines the priority of each indicator based on expert opinions (Feng et al, 2014;Mandić et al, 2021); rate each from 1, 3, 5, 7, and 9 to indicate the relative importance, and then Liu et al Computational Urban Science (2022) 2:32 constructs a judgment matrix. Then deter-mine the maximum eigenvalue of the comparison judgment matrix and its eigenvector (Clark & Tilman, 2017).…”
Section: Ahp and Ewm Combination Based On A Temporal Weight Matrixmentioning
confidence: 99%
“…The technical criterion relates to the use of the fuel on board and includes machinery (and machinery) modifications, fuel storage conditions, supply and infrastructure constraints (Brynolf, 2014;Thomson et al, 2015;Svanberg et al, 2018;Hansson et al, 2019Andersson et al, 2020). One study concluded that technical conditions are accepted as the most important criteria by shipowners (Mandić et al, 2021).…”
Section: Assessment Of Criteria For Alternative Marine Fuelsmentioning
confidence: 99%
“…In addition, human health indirectly falls within the scope of this criterion(Brynolf, 2014;Thomson et al, 2015;Svanberg et al, 2018;Hansson et al, 2019Andersson et al, 2020). The environmental criterion is most accepted among academicsBilgili (2022) Marine Science and Technology Bulletin 11(3): 352-360355(Mandić et al, 2021). This criterion constitutes a very important basis for the existence of alternative fuels, and the compliance of alternative fuels with existing and then potential environmental regulations has a primary priority.…”
mentioning
confidence: 99%